Magnetic resonance imaging of the prostate at 1.5 versus 3.0 T: A prospective comparison study of image quality. Issue 90 (May 2017) - Ullrich, T.; Quentin, M.; Oelers, C.; Dietzel, F.; Sawicki, L.M.; Arsov, C.; Rabenalt, R.; Albers, P.; Antoch, G.; Blondin, D.; Wittsack, H.J.; Schimmöller, L.
Highlights: Objective IQ for T2WI was at 1.5 T under optimized parameters comparable to 3 T. SNR and CNR of DWI were significantly higher at 3 T. Subjective IQ on was significantly better at 3 T. PI-RADS v2 scores were similar at 3 T and 1.5 T. Abstract: Objectives: This study prospectively evaluates objective image quality (IQ), subjective IQ, and PI-RADS scoring of prostate MRI at 3.0 T (3T) and 1.5 T (1.5T) within the same patients. Methods: Sixty-three consecutive patients (64 ± 9 years) were prospectively included in this non-inferiority trial, powered at 80% to demonstrate a ≤10% difference in signal-to-noise (SNR) and contrast-to-noise ratio (CNR) of T2-weighted and diffusion-weighted imaging (T2WI, DWI) at 1.5 T compared to 3 T. Secondary endpoints were analysis of subjective IQ and PI-RADS v2 scoring. Results: All patients received multi-parametric prostate MRI on a 3 T (T2WI, DWI, DCE) and bi-parametric MRI (T2WI, DWI) on a 1.5 T scanner using body coils, respectively. SNR and CNR of T2WI were similar at 1.5 T and 3 T (p = 0.7–1), but of DWI significantly lower at 1.5 T (p < 0.01). Subjective IQ was significantly better at 3 T for both, T2WI and DWI (p < 0.01). PI-RADS scores were comparable for both field strengths (p = 0.05–1). Inter-reader agreement was excellent for subjective IQ assessment and PI-RADS scoring (k = 0.9–1). Conclusion: Prostate MRI at 1.5 T can reveal comparable objective image quality in T2WI, but is inferior to 3 T in DWI and subjective IQ. However, similar PI-RADS scoring and thus diagnostic performance seems feasible independent of the field strength even without an endorectal coil.